Aspekte van Stoker se kritiek op die Wysbegeerte van die Wetsidee1 - Schulze, L.F. (Koers, 1994)
Some points of Stoker’s criticism of the Philosophy of the Creational Ide. Stoker had appreciation for many aspects of the Calvinist philosophy of Vollenhoven and Dooyeweerd, as is evident inter alia from his articles in Die Wagtoring (1932-1933) and in Koers (1937-1941). Yet, he also had some misgivings about the new philosophy. Some of his reservations, illustrating his independence as philosopher, are treated in this article, viz. (I) his criticism o f the 'law-idea’; (2) his rejection o f the notion that theology is a special science (vakwetenskap), and (3) his remarks that some humanistic and idealistic elements are incorporated in the Calvinist philosophy of Vollenhoven and Dooyeweerd. To undercut these deficiencies in the philosophy of Vollenhoven and Dooyeweerd he proposed his Philosophy of the Creational Idea.